Extraction, Isolation and Physico-Chemical Charaterization of Fenugreek Seed Mucilage - Sharma, Meenakshi; Arora, Kunal (Journal of Neonatal Surgery, 2025)
The purpose of this study is to prepare and assess a novel, affordable, and potent natural mucoadhesive agent that may be employed as a successful substitute for conventional mucoadhesive agents. The study's methodology comprised extracting the mucoadhesive agent from Trigonella foenumgraecum (fenugreek) seeds, assessing the mucilage's solubility, testing chemical properties such as presence of saponins and other bioactive constituents of fenugreek include mucilage, volatile oils, and alkaloids as well as physical properties like pH, swelling index, loss on drying, micromeritics property and FT-IR. The study found that the presence of mucilage, alkaloids, proteins and carbohydrate. pH of the polysaccharide was found to be 6.3+0.3,Swelling index was 9+0.2 ,loss on drying was contains 7.54 of moisture content. The Bulk density and the Tapped density were found to be 0.42+0.5gm/cm3 and 0.53+0.2gm/cm3 respectively .Carr’s index (%) and Hausner’s ratio of given polysaccharide was found to be 20.75 and 1.26, whereas the Angle of repose was 31.79. Polysaccharide shows the maximum solubility in Distilled water and Buffer of pH 6.8 which indicates the polysaccharide was soluble in inorganic solvent whereas in case of organic solvents i.e. Xylene and Petroleum ether it was insoluble. Interpretation of FTIR spectrum of Trigonellafoenum-graecum polysaccharide was:–OH stretch (3656.78), -C-H (3150.50),-C=C (2313.46), -C-H bend (1636.49), -C-H rock (1617.20), -CH bend out of plane (1029.45). FT-IR data is in accordance to that the essential group of polysaccharide was present.